2020
DOI: 10.1016/j.desal.2020.114627
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic assessment of solar energy coupling with large-scale desalination plant: The case of Morocco

Abstract: This paper examines the cost competitiveness of an extra-large-scale (275,000 m 3 /d) solar-powered desalination, taking as a case study the Chtouka Ait Baha plant in Morocco. It assesses the conditions at which solar Photovoltaics (PV) and Concentrated Solar Power (CSP) would be competitive with a grid (mainly fossil) driven desalination plant for the reference year and by 2030. The paper considers also a scenario where battery storage complements PV power generation. To conduct the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 36 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…cost of about $1/m 3 on average is affordable. Furthermore, this study and other studies indicated that solar energy is cost-effective when used in RO desalination plants(Kaya et al, 2019;Kettani & Bandelier, 2020). Compared to other MENA countries, the water cost of $1/m 3 is higher than the cost in those countries in general where desalinated water costs $0.5/m 3 with RO and except for thermal systems where the water cost subsidies on water tariffs would make solar-powered RO economically viable, attracting more adoption and more bene ts(Rachid et al, 2015;Trieb & Müller-Steinhagen, 2008).On the other hand, compared to other MENA countries, solar energy supply is favored over other renewable energy sources due to both sunlight availability and different water salinity, especially in countries bordering the Mediterranean Sea.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…cost of about $1/m 3 on average is affordable. Furthermore, this study and other studies indicated that solar energy is cost-effective when used in RO desalination plants(Kaya et al, 2019;Kettani & Bandelier, 2020). Compared to other MENA countries, the water cost of $1/m 3 is higher than the cost in those countries in general where desalinated water costs $0.5/m 3 with RO and except for thermal systems where the water cost subsidies on water tariffs would make solar-powered RO economically viable, attracting more adoption and more bene ts(Rachid et al, 2015;Trieb & Müller-Steinhagen, 2008).On the other hand, compared to other MENA countries, solar energy supply is favored over other renewable energy sources due to both sunlight availability and different water salinity, especially in countries bordering the Mediterranean Sea.…”
supporting
confidence: 56%
“…It is suggested that building many CSP driven RO plants would make building a CPS line cheaper and provide RO plants with the CSP advantage of storing heat at a lower cost. Meanwhile, studies have shown that the best alternative is to combine grid and solar energy when only solar power supply is not adequate(Filippini et al, 2019;Kettani & Bandelier, 2020). On the other hand, the CSP-powered plant's economic feasibility in Jordan is challenged by subsidized water tariffs up to 80% lower cost than the actual cost, making it economically unviable to run (Al-Addous et al, 2020).…”
mentioning
confidence: 99%
“…A specific yield of 1400 kWh/kWp [48,49,50] results in a specific capital cost of 0.32-0.46 $/kWh (SpCost PV ). The annual PV capital cost depends on the specific PV capital cost, the total MSED work in kWh/m 3 , ẆMSED , and the annual desalination capacity accounting for a 95% capacity factor [51,52]:…”
Section: Msed Capital Costsmentioning
confidence: 99%
“…As APV systems become more widely available, this initial investment cost is expected to decrease substantially. 56 and maintenance that are associated with system design for ammonia synthesis from waste nitrates. 10 These financial barriers again highlight the necessity of an external incentive, such as an emission fee, to incentivize the proposed concept toward economic viability.…”
Section: Resultsmentioning
confidence: 99%